Julian Higuera-Florez on harnessing environmental peacebuilding in Latin America and the Caribbean - Higuera-Florez, Julian; Soderberg, Angus (2025)
Environmental peacebuilding offers a promising framework to address deeply intertwined environmental challenges and conflict dynamics in Latin America and the Caribbean. So why has it not delivered fully on this promise? In an interview with ESCP, Julian Higuera-Florez, a research specialist in climate, peace, and security at the Alliance of Biodiversity and CIAT and CGIAR FOCUS Climate Security, discussed a new policy brief, Environmental Peacebuilding in Latin America and the Caribbean: Bridging Gaps and Harnessing Opportunities, co-authored with the UNDP Latin America and the Caribbean Hub.